1999
DOI: 10.1007/pl00009070
|View full text |Cite
|
Sign up to set email alerts
|

Long-term operation of continuous high cell density culture of Saccharomyces cerevisiae with membrane filtration and on-line cell concentration monitoring

Abstract: An internal membrane-®ltration bioreactor system with periodic fouling removal and on-line cell measurement was employed for long-term continuous ethanol production from glucose in order to prove its performance and practicality. The bioreactor system developed in this study was successfully operated for 2 months with no problems in the maintenance of ®ltration ux. The maximum productivity obtained in this study was about 13 g/l-h which was ca. 3.3 times higher than that obtained in a conventional chemostat wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The best experimental results reported so far have been obtained from single-stage chemostat systems with a membrane module [6,7]. With a microfiltration system, Groot et al [5] demonstrated that the ethanol productivity could be increased to 55 g l À1 h À1 with concomitant ethanol and glucose concentrations of 53 and 183 g l À1 , respectively.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The best experimental results reported so far have been obtained from single-stage chemostat systems with a membrane module [6,7]. With a microfiltration system, Groot et al [5] demonstrated that the ethanol productivity could be increased to 55 g l À1 h À1 with concomitant ethanol and glucose concentrations of 53 and 183 g l À1 , respectively.…”
Section: Introductionmentioning
confidence: 82%
“…This ethanol productivity was very high, but such a configuration may be unrealistic for industrial implementation since substrate cost represents 60% of the global cost. Park et al [7] succeeded in the total glucose conversion: a maximum ethanol productivity about 13 g l À1 h À1 was reported with an ethanol concentration of 43 g l À1 . Combining industrial criteria such as ethanol titre, ethanol productivity and residual substrate concentration, the performance reported here is one of the highest mentioned in the literature.…”
Section: Xt1_exp Xv1_expmentioning
confidence: 99%
“…With increasing agitation speed the flux also increased. In a later publication the long term behavior of the concept was investigated [10] and the operation was successfully operated for about two months.…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation problems can be solved to a considerable degree by decreasing the amount of stillage, which can be achieved by using the membrane bioreactors for ethanol production 8,9 . The membrane separation retains yeast cells in the bioreactor, which facilitates the ethanol distillation from the obtained filtrate.…”
Section: Introductionmentioning
confidence: 99%